2021
DOI: 10.1002/smi.3104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an evidence‐based nursing intervention on prevention of anxiety and depression in the postpartum period

Abstract: Postpartum depression has been one of the most common psychological disorders in patients during postpartum period. The constant anxiety and depression during this period seriously affect the physiological and psychological health of both the mother and infant. Evidence-based nursing has been widely applied in clinical practice and has achieved remarkable results. However, the effect of evidencebased nursing on postpartum depression remains unclear. Pregnant women who were not diagnosed with postpartum depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Evidence‐based nursing is based on nursing problems in clinical practice, analysing a large amount of clinical information and summarising it with their own experience, improving the personal skills and clinical experience of nursing staff and laying a solid foundation for the development of personalised nursing programmes by nursing staff 11,12 . Evidence‐based nursing has gradually emerged in the field of nursing in recent years, getting rid of the traditional nursing concepts that used to be based purely on experience and intuition, and playing an important role in the rapid development of the nursing profession, which has made a breakthrough in obstetrics and gynaecology, orthopaedics, cardiovascular internal medicine and intensive care medicine 13–16 . Therefore, we conducted this study aimed to evaluate the effect of evidence‐based nursing on post‐caesarean section wound infection, and to provide an objective evidence‐based medical basis for future clinical nursing work.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence‐based nursing is based on nursing problems in clinical practice, analysing a large amount of clinical information and summarising it with their own experience, improving the personal skills and clinical experience of nursing staff and laying a solid foundation for the development of personalised nursing programmes by nursing staff 11,12 . Evidence‐based nursing has gradually emerged in the field of nursing in recent years, getting rid of the traditional nursing concepts that used to be based purely on experience and intuition, and playing an important role in the rapid development of the nursing profession, which has made a breakthrough in obstetrics and gynaecology, orthopaedics, cardiovascular internal medicine and intensive care medicine 13–16 . Therefore, we conducted this study aimed to evaluate the effect of evidence‐based nursing on post‐caesarean section wound infection, and to provide an objective evidence‐based medical basis for future clinical nursing work.…”
Section: Introductionmentioning
confidence: 99%
“…EBN has played an important role in the rapid development of the nursing profession, leading to breakthroughs in obstetrics and gynaecology, orthopaedics, cardiovascular medicine and intensive care. 10 , 11 , 12 , 13 Khan et al found that the introduction of an EBN programme during the perioperative period in patients undergoing appendectomy resulted in a significant reduction in the length of stay in hospital and in hospital costs. 14 Therefore, we speculate that EBN may have a positive significance on the recovery of patients with AA.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence-based nursing (EBN) intervention is a nursing strategy that uses credible scientific research results as evidence in combination with patient needs to implement patient care, providing patients with personalized nursing services. 6 , 7 EBN has been widely applied in clinical practice and makes great progress in the management of diseases such as chest pain, 8 postpartum depression 6 and acute coronary syndrome. 9 For stroke, previous studies have shown that using EBN theories could reduce the morbidity and mortality associated with stroke.…”
Section: Introductionmentioning
confidence: 99%